2022
DOI: 10.1021/acsnano.1c11578
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Actively Transport Nanoparticles in Tumors After Extravasation

Abstract: Nanoparticles need to navigate a complex microenvironment to target cells in solid tumors after extravasation. Diffusion is currently the accepted primary mechanism for nanoparticle distribution in tumors. However, the extracellular matrix can limit nanoparticle diffusion. Here, we identified tumor-associated macrophages as another key player in transporting and redistributing nanoparticles in the tumor microenvironment. We found tumor-associated macrophages actively migrate toward nanoparticles extravasated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…Although this was observed for both NP sizes, only the animals administered with 60 nm NPs showed any significance ( p < 0.05). This size-dependent uptake of NPs by macrophages is in line with recent data, where it has been shown that smaller NPs are less internalized by CD11b + phagocytes compared to larger ones. In both cases, the lower levels of TAMs were still able to phagocytose significantly more NPs compared to the control ( p < 0.01).…”
Section: Resultssupporting
confidence: 91%
“…Although this was observed for both NP sizes, only the animals administered with 60 nm NPs showed any significance ( p < 0.05). This size-dependent uptake of NPs by macrophages is in line with recent data, where it has been shown that smaller NPs are less internalized by CD11b + phagocytes compared to larger ones. In both cases, the lower levels of TAMs were still able to phagocytose significantly more NPs compared to the control ( p < 0.01).…”
Section: Resultssupporting
confidence: 91%
“…NPs with smaller sizes (15, 50, and 100 nm in this experiment) tended to diffuse for transport in the TME. [ 73 ] This study provides another possibility to reconsider the TAMs in the TME.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…This is because plasma proteins (e.g., immunoglobulins, adhesion mediators, complement proteins) may act as opsonins to bind with the nanomaterials, leading to e cient phagocytosis by macrophages 36,41,42 . Considering the slow blood ow in the dense capillary network inside marrows 37,43 , the local macrophages take their time to capture nanoparticles and transport them to a distance from the vessels 44 .…”
Section: Resultsmentioning
confidence: 99%